Assessment of Autozygosity Derived From Runs of Homozygosity in Jinhua Pigs Disclosed by Sequencing Data - Xu, Zhong; Sun, Hao; Zhang, Zhe; Zhao, Qingbo; Olasege, Babatunde Shittu; Li, Qiumeng; Yue, Yang; Ma, Peipei; Zhang, Xiangzhe; Wang, Qishan; Pan, Yuchun (Frontiers in Genetics, 2019)
Jinhua pig, a well-known Chinese indigenous breed, has evolved as a pig breed with excellent meat quality, greater disease resistance and higher prolificacy. The reduction in the number of Jinhua pigs over the past years has raised concerns about inbreeding. Runs of homozygosity (ROH) along the genome has been applied to quantify individual autozygosity to improve the understanding of inbreeding depression and identify genes associated with traits of interest. Here, we investigated the occurrence and distribution of ROH using next-generation sequencing data to characterize autozygosity in 202 Jinhua pigs as well as to identify the genomic regions with high ROH frequencies within individuals. The average inbreeding coefficient based on ROH longer than 1Mb was 0.168 ± 0.052. In total, 18,690 ROH were identified in all individuals, among which shorter segments (1-5Mb) predominated. Individual ROH autosome coverage ranged from 5.32% to 29.14% in Jinhua population. On average, approximately 16.8% of the whole genome was covered by ROH segments, with the lowest coverage on SSC11 and the highest coverage on SSC17. A total of 824 SNPs (less than 1%) and 11 ROH islands regions were identified (occurring in over 45% of the samples). Genes associated with reproduction (HOXA3, HOXA7, HOXA10 and HOXA11), meat quality (MYOD1, LPIN3 and CTNNBL1), appetite (NUCB2) and disease resistance traits (MUC4, MUC13, MUC20, LMLN, ITGB5, HEG1, SLC12A8 and MYLK) were identified in ROH islands. Moreover, several quantitative trait loci (QTL) for ham weight and ham fat thickness were detected. Genes in ROH islands suggested, at least partially, a selection for economic traits and environmental adaptation, and should be subject of future investigation. These findings contribute to the understanding of the effects of environmental and artificial selection in shaping the distribution of functional variants in pig genome.